Shifting the aquaculture regime toward gender equity? Case studies of women’s entrepreneurial niche innovations in Bangladesh - Choudhury, Afrina; Leeuwis, Cees; van der Burg, Margreet; McDougall, Cynthia; Adam, Rahma (Taylor & Francis (Routledge), 2025)
Efforts to promote women’s participation, benefits, and empowerment in aquaculture entrepreneurship face persistent challenges rooted in patriarchal norms, policy frameworks, and local contexts. This article investigates how women’s entrepreneurship, supported by targeted programs, can help address these entrenched barriers. To do so, we employ the multi-level perspective (MLP) framework, which examines women’s entrepreneurial “niches” in relation to the dominant “regime” of local policies, public action, and gender norms. Our central aim is to understand how supporting women’s entrepreneurship can drive systemic change within aquaculture. Using a governance framework, we analyze strategies applied in two pilot interventions in Bangladesh, seeking to identify the limitations of current governance approaches and to propose strategies for establishing a more gender-equitable aquaculture regime. Our analysis reveals that existing strategic frameworks often fail to capture the agentic actions women take prior to program implementation and do not sufficiently address the influence of social and gender norms. Based on our findings, we recommend integrating gender transformative approaches and agentic strategies into governance frameworks, with the goal of challenging the prevailing regime and fostering greater gender equality in aquaculture. This approach recognizes women’s proactive roles and the importance of reshaping governance to support systemic gender equity.